Characteristics Of Leper Disease: Literature Review - Dwi Yupitasari Sunarto; Nurelly Noro Waspodo; Asrini Safitri (Jurnal EduHealth, 2024)
According to the World Health Organization (WHO), leprosy is a chronic infectious disease that attacks the skin and peripheral nerves caused by Mycobacterium Leprae. Leprosy or what is known as Morbus Hansen can occur in all age groups, several other factors are thought to contribute to the increase in leprosy cases, one of which is age, gender, type of leprosy, education, employment and socio-economic factors. The aim of this literature is to determine the characteristics of leprosy. The research method used in the results of this research is Literature Review or literature review. Related keywords are "characteristics, leprosy". Search the Internet for this research article via accesses such as Google Scholar, Pubmed, and ScienceDirect. The research results show that from 10 journals, leprosy can occur at any age. However, in the economically active age, the most incidents are found in the age category, namely 30-60 years. Where the incidence rate in men is higher than in women. Other research shows that leprosy is a multibasilar type, which indicates that it is due to late diagnosis and the connection between poverty and lack of knowledge which causes leprosy to continue to spread.